Effects of Age and Method of Drying on the Proximate Composition of Housefly Larvae (Musca domestica Linnaeus) Meal (HFLM) - Aniebo, A.O.; Owen, O.J. (Pakistan Journal of Nutrition, 2010)
The effects of age at which House Fly Larvae (HFL) is harvested and method of drying the larvae, on its proximate values were studied. Larvae were harvested on three different days representing three different ages and the harvested larvae were dried using both oven and sun light. Results revealed that protein content of HFL processed into meal after drying significantly (p<0.05) reduced as the age of larvae increased from 55.4% on 2 day old, through 50.2% on three-day old, to 47.1% on four day old. On the other hand, fat content increased with increase in age of HFL, from 20.8% at age of 2 days, through 22.2% at age of 3 days to 25.3% at the age of 4 days. Fibre content minimally increased with age. Oven-dried maggots had mean higher protein content (50.9%) and less fat (22.8%) than sun dried maggots (47 and 26.4% respectively). Therefore, for maximum protein yield, HFL should be harvested at 2 days old. However, where maggot fat is needed in a diet, increased biomass and or ease of harvesting, processing at later age (4 days old) became desirable. Oven-drying is recommended for superior protein and in rainy season, while sun drying produced higher fat and was cheaper.